Dowody na istnienie Boga - Białas, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The increased interest in arguments for the existence of God appeared in the XI century, with the development of the dialectic. One of the most famous ontological proof is a proof of Anselm of Canterbury – to prove the existence of God by going out only with HIS idea. In the XIII century, the ontological argument has lost its importance to the „five ways” of the Saint Thomas Aquinas, inspired by Aristotle and based on experience.